Representation of Millennial Generation in Dalang Pelo’s Animation: An Overview of Narrative and Visual Aspects - Lestari Kusuma Dewi; Aswan Aswan (2021)
Each animator has a characteristic in framing the story and visuals in their animated film. This phenomenon is interesting to study considering that currently the millennial generation dominates animated films. This study aims at describing how the millennial generation is represented by the animation of Dalang Pelo. This study uses a qualitative research method with a descriptive analysis. The findings in this study are the representations of themillennial generation through narrative and visual aspects in the animated film Dalang Pelo. The animator represents the narrative story in a simple animation with three acts, and this shows that the millennial generation does not like complicated things. Findings from the aspect of cinematography are used to support dramatic functions, narrative delivery, and story themes in animation that viewers, especially the millennial generation, who tend to be easily carried away with feelings can enjoy the story.